Quantitative mineral resource assessment of copper, molybdenum, gold, and silver in undiscovered porphyry copper deposits in the Andes Mountains of South America - Cunningham, Charles G. (2008)
Prepared and published jointly by the geological surveys of Argentina, Chile, Colombia, Peru, and the United States